Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Pada Generasi Milenial Program Studi Pendidikan Ekonomi Universitas Muhammadiyah Bengkulu - Erwani Yusuf; Peni Melasari (Universitas Dehasen Bengkulu, 2022)
This study aims to determine whether the factors of motivation, innovation, creativity, self-confidence and science of technology affect the entrepreneurial interest of students of the Economic Education Study Program, University of Muhammadiyah Bengkulu. This type of research is a quantitative study with a total sample of students from the 2018 and 2019 classes so that the number of respondents is 71. Data collection techniques using observation, questionnaires and documentation. The data analysis technique used multiple linear regression analysis with the SPSS version 26.0 program. The results showed that the motivation indicator had a tcount of 4,555 with a cronbach alpha of 85.2%, then the innovation variable had a tcount of 5.685 with a cronbach alpha of 84.2%, creativity with a tcount of 7,316 with a cronbach alpha of 88,1%, confidence tcount of 17,428 with cronbach alpha 84.3% and technology science with a value of tcount 5.299 with cronbach alpha 87.4%. While the value of the coefficient of determination (R2) is 0.823, which means that 82.3% of these factors affect students' interest in entrepreneurship.